M.F. Force letter - Force, M. F. (Manning Ferguson), 1824-1899.
ALS (13 February 1852; Shady Hill, Cambridge, Mass.) to Force from Charles Eliot Norton providing details of his and others' opinions of the Kansas-Nebraska Bill. Norton also mentions Henry Wadsworth Longfellow's resignation of his professorship at Harvard University and the possibility of Samuel Eliot replacing him, and reviews Julia Ward Howe's book of poetry titled, Passion Flowers (1854).
U.S. Army officer, lawyer, and historian.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Eliot, Samuel, -- 1821-1898.; Howe, Julia Ward, -- 1819-1910.; Longfellow, Henry Wadsworth, -- 1807-1882.; Norton, Charles Eliot, -- 1827-1908 -- Correspondence; Harvard University -- Faculty; United States; American poetry; Missouri compromise; Slavery -- United States; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1815-1861.; Army officers; Historians; Lawyers